Environmental and financial assessment of producing bioenergy from Bambusa balcooa, Anogeissus leiocarpa and Senna siamea in Ghana. (1st December 2020) - Akoto, Daniel S.; Partey, Samuel T.; Denich, Manfred; Kwaku, Michael; Borgemeister, Christian; Schmitt, Christine B.
Abstract: To evaluate environmental impacts and financial profitability of producing 1 MJ energy of charcoal from bamboo - Bambusa balcooa in comparison with two commonly used local species - Anogeissus leiocarp a and Senna siamea were analyzed. Environmental impacts were assessed using the Life Cycle Analytical (LCA) approach while financial viability of the various systems was evaluated using the financial benefit cost ratio (FBCR) and net present value (NPV). Emissions from all the charcoal production stages were calculated using GaBi 4 LCA software and the Ecoinvent V3 and Idemat 2015 life cycle inventory databases. Emission contributions from all four stages in the charcoal production cycle were analyzed using the CML 2001 method. Environmental impacts were analyzed based on the potential for global warming, atmospheric acidification, eutrophication, depletion of abiotic resources, human toxicity, ozone layer depletion and eco-toxicity. The LCA revealed that compared with S. siamea and A. leiocarpus, production of charcoal from B. balcooa (bamboo) was the more environmentally friendly option after S. siamea, recording lower in five out of the seven (86%) impact categories used in the LCA. This was attributed to the relatively low use of chemical inputs (fertilizer, pesticides, fossil fuel etc.) in the bamboo charcoal production cycle. Nonetheless, the financial analysis revealed that despite recording the lowest production cost, charcoal production from B. balcooa was least profitable (FBCR = 1.1) compared with the two traditional species. This was primarily due to the low market price of bamboo charcoal in the study region. While bamboo charcoal may be encouraged for purposes of environmental sustainability, increased sensitization on the economic potential of bamboo charcoal and the environmental benefits it brings may improve local adoption and market value. Graphical abstract: Image 1 Highlights: Bamboo is a viable alternate source of biomass for producing charcoal. Producing charcoal from bamboo is more environmentally friendly than local species. Charcoal production from bamboo is less costly compared to local species. Bamboo charcoal is less profitable due to low market price. Increased awareness on bamboo charcoal may improve local adoption and market value.